Partial cystectomy for bladder squamous cell carcinoma with a 10-year follow-up: a case report - Yin, Na; Zhao, Wei; He, Tao; Li, Tingchao; Lei, Xu; He, Hao; Long, Zongmin; Wang, Yan (Frontiers in Oncology, 2023)
Squamous cell carcinoma (SCC) of the bladder is a rare malignancy of the urinary system.It is prone to invasion and metastasis in the early stage and has a poor prognosis. This case reports a65-year-old female patient with SCC of the bladder who was free of disease recurrence and metastasis 10 years after partial cystectomy (PC) combined with left ureteral reimplantation. The treatment plan and admission of this patient were retrospectively analyzed in order to provide some reference significance for the treatment plan of SCC of the bladder.